Weed Management in Conservation Agriculture - Sar , Koushik; Padhi , Ipsita (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
Given the current scarcity of natural resources and the unpredictable nature of the climate, conservation agriculture (CA) is a practical alternative. As a result, it is increasingly being used in rainfed areas to conserve soil and water. Herbicide use or manual weeding is both effective ways to manage the weed problem in CA. In conservation agriculture, weed control is greatly influenced by tillage, crop establishment methods, machinery, agronomic practices, etc. Conservation farming places a strong priority on resource preservation and prohibits the use of chemicals. Under conservation agriculture, weeds can be reduced by using crop rotation, compatible type selection with optimal seed rates, tillage with sufficient soil leveling, cover crops, and appropriate water management. In CA, the use of herbicides has increased because of high labor costs and timely unavailability. The sustainability of conservation agriculture can be improved by implementing integrated weed management, as a single herbicide cannot effectively control a wide variety of weeds.